Application of image processing techniques in computer graphics algorithms - Rokita, Przemyslaw (Computer networks and ISDN systems, 1997)
Image processing is usually associated with pattern recognition and is rather treated as a subject outside of the computer graphics interest. Basically computer graphics algorithms are used for the visualization of scenes or models described using some abstract notation, while image processing is used on the opposite way — i.e. when finding an abstract description of an analyzed pattern. This paper proposes to use the image processing approach for rendering optical effects in computer graphics algorithms. Proposed algorithms can be used for the generation of realistic and artistic optical effects in real-time, in, for example, visual simulators, virtual reality or multi-media applications.